REVOLUTIONIZING RENEWABLE ENERGY AN INNOVATIVE DESIGN OF ARCHIMEDES WIND TURBINE INTEGRATED WITH SOLAR PANELS - Sihmaulana Dwianto; Ardianto Syaifur Rohman; Tunjung Genarsih; Audha Fitrah Aulina (Scientific Journal of Mechanical Engineering Kinematika, 2025)
This study aims to analyze the structural strength and aerodynamic performance of an Archimedes Screw Wind Turbine (ASWT) integrated with solar panels as a hybrid renewable energy system. The methodology includes static simulations using Finite Element Analysis (FEA) and Computational Fluid Dynamics (CFD) simulations conducted with Ansys software. The turbine design consists of three spiral blades made of aluminum 6061-T6, with key parameters: an outer diameter of 300 mm, blade length of 137.4 mm, blade thickness of 1.5 mm, and a tilt angle of 65°. Wind loads were applied at speeds ranging from 50–100 m/s from frontal and lateral directions, as well as on the support structure. The static simulation results showed maximum stresses of 19.8 MPa (frontal), 27.67 MPa (lateral), and 2.6 MPa (support), all well below the material’s yield strength of 276 MPa. CFD simulations with a 7 m/s inlet velocity and tip speed ratio (TSR) ranging from 4 to 10 indicated optimal aerodynamic performance at TSR values of 7–8. Efficiency decreased at higher TSR due to solid wall effects and wake vortex formation. Overall, the ASWT-solar panel design is structurally safe and aerodynamically efficient, though further optimization of blade geometry and TSR control is recommended to enhance system performance.